The intrinsic axon regenerative properties of mature neurons after injury. (23rd December 2020) - Liu, Chunfeng; Liu, Jinlian; Liu, Chaoqun; Zhou, Qing; Zhou, Yaodong; Zhang, Boyin; Saijilafu,
Abstract: Thousands of nerve injuries occur in the world each year. Axon regeneration is a very critical process for the restoration of the injured nervous system's function. However, the precise molecular mechanism or signaling cascades that control axon regeneration are not clearly understood, especially in mammals. Therefore, there is almost no ideal treatment method to repair the nervous system's injury until now. Mammalian axonal regeneration requires multiple signaling pathways to coordinately regulate gene expression in soma and assembly of the cytoskeleton protein in the growth cone. A better understanding of their molecular mechanisms, such as axon regeneration regulatory signaling cascades, will be helpful in developing new treatment strategies for promoting axon regeneration. In this review, we mainly focus on describing these regeneration-associated signaling cascades, which regulate axon regeneration.